CURRENTS AND STYLES OF ECOLOGICALLY-BASED AGRICULTURE IN BRAZIL: ORIGINS, CONTEXTS, SUBJECTS, AND ORGANIZATIONS (Interdisciplinary Studies Journal, 2024)
This work analyzes the currents and styles of Ecologically-Based Agriculture in Brazil, investigating its origins, contexts, subjects and organizations involved. It aims to understand how these sustainable practices are being implemented in the country and identify the challenges faced by social movements, institutions and individuals in promoting these styles of agriculture. The methodology used was Systematic Literature Mapping in the Google Scholar, Portal de Periódicos da CAPES, Scielo and Redalyc databases. Publications were screened between 1992 and 2023, using the search string “alternative agriculture” AND “ecologically based agriculture” AND “Brazil”; and their equivalents in English and Spanish. From this screening, an active search was carried out for the descriptors: “organic agriculture”, “ecological agriculture”, “permaculture”, “biodynamic agriculture” and “natural agriculture”, with the selection of 30 relevant publications for analysis. The results point to the diversity of Ecologically-Based Agriculture currents in Brazil, each with its own particularities and contributions to the sustainability of agriculture in the country. The fundamental role of social movements, popular education and agroecology in promoting these practices and the need to build organizational processes and appropriate technologies for greater dissemination of these styles of agriculture throughout the country is highlighted.
Keywords: Organic Agriculture; Ecological Agriculture; Permaculture; Biodynamic Agriculture; Natural Agriculture